Behavioral laterality of the brain: support for the binary construct of hemisity - Morton, Bruce E. (Frontiers in Psychology, 2013)
Three terms define brain behavioral laterality: Hemispheric dominance identifies the cerebral hemisphere producing one’s first language. Hemispheric asymmetry locates the brain side of non-language skills. A third term is needed to describe a person’s binary thinking, learning, and behaving styles. Since the 1950s split-brain studies, evidence has accumulated that individuals with right or left brain behavioral orientations (RPs or LPs) exist. Originally, hemisphericity sought, but failed, to confirm the existence of such individual differences, due to its assertion that each individual lay somewhere on a gradient between competing left and right brain extremes. Recently, hemisity, a more accurate behavioral laterality context, has emerged. It posits that one’s behavioral laterality is binary: i.e., inherently either right or left brain-oriented. This insight enabled the quantitative determination of right or left behavioral laterality of thousands of subjects. MRI scans of right and left brain-oriented groups revealed two neuroanatomical differences. The first was an asymmetry of an executive element in the anterior cingulate cortex. This provided hemisity both a rationale and a primary standard. RPs and LPs gave opposite answers to many behavioral preference “either-or”, forced choice questions. This showed that several sex vs. hemisity traits are being conflated by society. Such was supported by the second neuroanatomical difference between the hemisity subtypes, that RPs of either sex had up to three times larger corpus callosi than LPs. Individuals of the same hemisity but opposite sex had more personality traits in common than those of the same sex but different hemisity. Although hemisity subtypes were equally represented in the general population, the process of higher education and career choice caused substantial hemisity sorting among the professions. Hemisity appears to be a valid and promising area for quantitative research of behavioral laterality.